Syringin, a phenylpropanoid glycoside alleviates Oxidative Stress in Rats with High-Fat Diet fed - STZ induced Hyperglycaemia - U.S. Mahadeva, Rao; Aung Myo, Oo @mohd Hashym; Thant, Zin (2019)
Background: Diabetic oxidative stress coexists with a reduction in the free radical scavenging status, which can further increase the detrimental effects of free radicals. Objective: To study the effect of syringin on the magnitudes of oxidative stress in high-fat-diet fed, low-dose streptozotocin (STZ) induced experimental diabetes (T2DM) in rats.